Rancang Bangun Purwarupa Sistem Parkir Otomatis Menggunakan RFID dan Sensor IR Proximity - Yahya Ega Masyarik; Danny Kurnianto; Nur Afifah Zen (Teknik Elektro Politeknik Negeri Padang, 2022)
Managers of universities have a responsibility to ensure that parking is available for all stakeholders, particularly students. When there is not enough parking space for the quantity of vehicles arriving, issues occur. Consequently, the atmosphere was no longer favorable due to the pandemonium of vehicles that had taken over. This research's objective is to create a working prototype of an vehicles parking system that can control the flow of vehicles into the campus area. This system's controller is a Wemos D1 Mini, which may be used with the ESP 8266 module to connect to the internet, RFID card for students' identities for drivers of motor vehicles, servo motors to control gateways, infrared proximity sensors to count the number of vehicless entering and exiting the parking area, and Google Firebase for student lecture scheduling databases are all examples of technology used in parking area today. The test results reveal that the system can successfully verify the schedule saved in Firebase and read the student's identity contained on the RFID card. Only students with class schedules on that day are permitted access to the parking area.